Corporate Accountability in Environmental Crimes: Lessons from Indonesia's Forest Fires and Beyond - Sujono Sujono; Istianingsih Istianingsih (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Indonesia, home to over 125 million hectares of tropical rainforests, is a critical player in global climate regulation and biodiversity conservation. However, environmental crimes, such as forest fires, illegal logging, and industrial pollution, have caused severe ecological degradation, public health crises, and significant economic losses. This study examines systemic gaps in Indonesia's environmental governance, focusing on the effectiveness of judicial processes, the proportionality of penalties, and the role of international frameworks. Through a qualitative analysis of high-profile cases, including PT Adei Plantation and PT Kalista Alam, the research highlights key deficiencies in enforcement mechanisms, such as delayed judicial decisions, insufficient penalties, and limited integration of global sustainability frameworks. The findings underscore the need for recalibrating penalties, streamlining judicial processes, and leveraging international agreements to strengthen corporate accountability. This study contributes to the broader discourse on environmental governance by providing actionable recommendations to align Indonesia’s enforcement mechanisms with global best practices, ensuring sustainable development and climate resilience.